2019
DOI: 10.1007/s40620-019-00661-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations between small and middle molecules clearance and the change of cognitive function in peritoneal dialysis

Abstract: Background Uremic toxins have been suspected as potential contributors for cognitive impairment in peritoneal dialysis (PD) patients. However, associations between the clearance of serum small and middle molecules and the change of cognitive function were not fully explored and then we explored this issue in the present study. Method A total of clinically-stable 222 patients on PD were enrolled and then followed up for 2 years in this single-center prospective cohort study. Small and middle molecules clearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Consistent with previous studies, our results revealed that dialysis-dependent ESRD patients have an increased risk of incident all-cause dementia/Alzheimer disease/vascular dementia compared to the GP. Pathophysiologic mechanisms for the occurrence and progression of dementia in patients with CKD and dialysis-dependent ESRD have been reported to be traditional risk factors like older age, hypertension, diabetes mellitus, dyslipidemia, and cardiovascular disease; nontraditional kidney disease-related factors such as albuminuria, retention of uremic toxin, anemia, and vascular calcification; and ESRD treatment-associated risk factors including intradialytic hypotension, cerebral edema, and thrombotic events [4,6,20,[24][25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous studies, our results revealed that dialysis-dependent ESRD patients have an increased risk of incident all-cause dementia/Alzheimer disease/vascular dementia compared to the GP. Pathophysiologic mechanisms for the occurrence and progression of dementia in patients with CKD and dialysis-dependent ESRD have been reported to be traditional risk factors like older age, hypertension, diabetes mellitus, dyslipidemia, and cardiovascular disease; nontraditional kidney disease-related factors such as albuminuria, retention of uremic toxin, anemia, and vascular calcification; and ESRD treatment-associated risk factors including intradialytic hypotension, cerebral edema, and thrombotic events [4,6,20,[24][25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiologically, KT may reverse the underlying mechanisms that cause cognitive impairment in ESRD patients, including nontraditional kidney disease-related factors and ESRD treatment-associated factors, as mentioned above [ 15 ]. A previous study reported that high middle molecule clearance rates improve general cognitive and executive functions in patients undergoing peritoneal dialysis [ 31 ]. Since insufficient middle molecule clearance (a limitation of current dialysis) is improved in post-KT patients, it may have an impact on the low incidence of dementia found.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of inflammatory mediators, including interleukins, induces cerebral inflammation and oxidative damages, causing excitotoxic injuries and the resultant neurodegeneration [76]. An enhanced clearance of middle molecules also correlates closely with a better cognitive performance and executive function in ESRD patients [77].…”
Section: Other Utsmentioning
confidence: 99%